KONSUMSI AIR KEMASAN INDONESIA - Lulu Lestari (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Water is primary need for human. People need at least 2 litres of water a day for drinking. Fulfilment of these needs very depend on the availability of a decent drinking water source. Based on data of Statistics Indonesia, people who consume bottled water in Indonesia reached 36 percent in 2018. It was significantly increase 3 times compared 10 years before. This increase needs to be watched out because bottled water is an unsustainable source of drinking water. In the following research, a model was formed that can predict the factors that influence bottled water consumption. The model was carried out using Structural Equation Modelling Partial Least Square (SEM PLS) analysis. The results from measurement model: demographic factor is measured by growth of population and urbanization, income factor measured by expenditure per capita per month, social culture factor measured by Human Development Index (HDI) and percentage of people who watch television. Based on structural model, all of the factors (demography, income, social culture) affect bottled water consumption in Indonesia. DKI Jakarta, Kepulauan Riau, Kalimantan Timur, Kalimantan Utara, and Kepulauan Bangka Belitung are the provinces which predicted have significant increasing in bottled water consumption.